Firms’ digital transformation and e-human resource management. A qualitative approach - Escribá-Carda, Naiara (2024)
In recent years, digital transformation processes have been gaining relevance. However, not all companies are achieving the same degree of transformation. The presence of barriers and enablers plays a significant role in this process. Furthermore, the extent of digital transformation also impacts how human resources (HR) policies are deployed and influences the effect they have on employees. This work aims to understand how the digital transformation process is occurring from a qualitative approach. Specifically, this study analyzes the main drivers and barriers of firms' digitalization, as well as its effects on companies, people, and human resource practices. Eight semi-structured interviews were conducted with key informants in three companies to gain an in-depth insight into the research problem. ATLAS.ti was used for data analysis and coding. Results show the presence of barriers and facilitators documented in existing literature. However, our results reveal that the business size and the firm's main activity are important variables that affect the extent of digital transformation. The study also reveals the benefits of digitalization in terms of efficiency and human resource autonomy (flexibility, work-life balance).  Likewise, the findings unveil the negative consequences of digitalization.